2017
DOI: 10.1002/aenm.201700130
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose‐based Supercapacitors: Material and Performance Considerations

Abstract: One of the biggest challenges we will face over the next few decades is finding a way to power the future while maintaining strong socioeconomic growth and a clean environment. A transition from the use of fossil fuels to renewable energy sources is expected. Cellulose, the most abundant natural biopolymer on earth, is a unique, sustainable, functional material with exciting properties: it is low‐cost and has hierarchical fibrous structures, a high surface area, thermal stability, hydrophilicity, biocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
171
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(175 citation statements)
references
References 155 publications
2
171
0
Order By: Relevance
“…6d, the specific capacitance of CS-DAC-C (derived from the GCD curves) was up to 242 F g -1 at a current density of 1 A g -1 , which was much higher than those obtained for DAC-C (181 F g -1 ) and LC-DAC-C (180 F g -1 ), and comparable to results previously reported for cellulose-based carbon electrodes (Chen et al 2014a;Jiang et al 2015Jiang et al , 2016Li et al 2016c). The higher capacitance of CS-DAC-C compared to LC-DAC-C was probably the result of the higher SSA of the former (Li et al 2016a, b;Wang et al 2017). The fact that the DAC-C electrode, which had the highest SSA of the samples under study, exhibited a lower capacity than CS-DAC-C indicates that the doped heteroatoms contributed more to the capacitive behavior than the SSA.…”
Section: Charge Storage Propertiessupporting
confidence: 66%
“…6d, the specific capacitance of CS-DAC-C (derived from the GCD curves) was up to 242 F g -1 at a current density of 1 A g -1 , which was much higher than those obtained for DAC-C (181 F g -1 ) and LC-DAC-C (180 F g -1 ), and comparable to results previously reported for cellulose-based carbon electrodes (Chen et al 2014a;Jiang et al 2015Jiang et al , 2016Li et al 2016c). The higher capacitance of CS-DAC-C compared to LC-DAC-C was probably the result of the higher SSA of the former (Li et al 2016a, b;Wang et al 2017). The fact that the DAC-C electrode, which had the highest SSA of the samples under study, exhibited a lower capacity than CS-DAC-C indicates that the doped heteroatoms contributed more to the capacitive behavior than the SSA.…”
Section: Charge Storage Propertiessupporting
confidence: 66%
“…Despite great success in the development of high‐performance electrodes based on a CNT or Graphene conductive percolation network, the limited production capacity and high cost of these 1D and 2D carbon additives make the electrodes less competitive than today's commercialized products. From the view point of production cost and capacity, cellulose, the most abundant natural polymer on earth, is highly competitive and attractive as a 1D building block for constructing thick electrodes . Recently, Kuang et al reported a highly conductive hybrid fiber based on abundantly available cellulose nanofibers (CNFs) and commercialized CBs as a 1D building block for constructing free‐standing thick electrodes ( Figure 8 a) .…”
Section: Integrated Electrode and Current Collectormentioning
confidence: 99%
“…It is worth mentioning that EDLC electrode performance depends on the type of cellulose used in the capacitors. According to Wang et al [42], cellulose microfibers (CMFs) are used to obtain electrodes with relatively low active mass loadings. In contrast, nanocellulose fiber (NCF)-and cellulose nanocrystal (CNC)-based electrodes indicate relatively high active mass loadings.…”
Section: Introductionmentioning
confidence: 99%